Proposed upgrading Poliklinik Permai at 6 KMPTD Bandar Baru Seri Iskandar, Daerah Perak Tengah,32600 Bota Perak Darul Ridzuan / Fatimah Ahmad - Ahmad, Fatimah (Faculty of Architecture, Planning and Surveying, 2011)
Interesting area can attract people's attention. The design provides good benefits and functionality to consumers will help improve the quality of life. Each student is taught to write the report in the correct way through the subject of INA 396 (Research Project and Report). All information on selected projects will be recorded in detail and give appropriate. All the process from start to finish will be recorded in detail to facilitate the readers understanding of the design space featured in the project. All problems and solutions are made will be described in more detail. Subject of INA 396 can help and give benefit to each student how to write reports in the correct way. It helps student to think more creative and analytical in developing a plan and selecting suitable way to understand the plan and space. This subject also gave early exposure to students how to write reports correctly and early preparation for writing a thesis for the degree, master’s and PhD level. Exposure at diploma level can help students on their studies at a higher level. Therefore, this subject should be retained because it provides tremendous benefits to each student.